Impact of COVID-19 on Tourism in Kenya: Strategies for Recovery - Ondicho, Tom (University of Nairobi, 2021)
Many tourists have cancelled their trips to Kenya in response to global travel restrictions due to COVID-19. Plummeting demand has triggered a crisis that is being felt throughout the entire tourism ecosystem. Most tourist activities and businesses have been closed, and others are operating at a lower level, resulting in massive revenue and job losses. Whilst tourism has proven to be resilient to shocks, including terrorism, violence, natural disasters, economic recession, and pandemics, none of the disruptive events has ever had such a phenomenal impact on the world’s economy, especially the tourism economy as COVID-19 (UNWTO, 2020). The impact of COVID-19 will most likely last longer, rendering the future bleak, and the road to recovery is uncertain, but much will depend on appropriate policy stimulus to mitigate the effects of COVID-19 and kickstart a rebirth of Kenya's tourism industry.
Keywords: COVID-19; Kenya; Tourism